Respon Negara-negara Asia Pasifik atas Kekerasan terhadap Perempuan pada Masa Pandemi Covid-19 - Rekha Kersana; Rini Afriantari; Bulbul Abdurrahman (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
Non-traditional security issues are increasingly relevant in international relations discussions nowadays. Threats do not only come from the military aspect but could also come from the climate crisis, terrorism and global pandemic. As happened recently, countries in the Asia Pacific are facing a non-traditional threat, namely Covid-19, which threatens all aspects of human security, especially health security. At the same time, several countries have implemented lockdown, but this policy has resulted in violence against women. This is certainly an issue that must be resolved by countries in the Asia Pacific region, as well as UN Women as an international organization that is responsible for issues concerning basic rights for women. In this study, the authors analysed the response that shown by countries in the Asia Pacific. The results of this study indicate that violence against women in the Asia Pacific was triggered by, among others: (1) the increasing interaction between victims and perpetrators, (2) environments that trigger acts of violence, and (3) limited support services. Thus, the authors examined how the policy responses of Asia Pacific countries in resolving the violence against women that occurred during the Covid-19 pandemic.